Individually Directed some Features of Technology - Shomirzaev Maxmatmurod Xuramovich (Genius Journals, 2022)
The article deals with the issue of directing students to work and career choices using elements of the Uzbek national handicrafts in school technology education in a logical sequence through the conference lesson
Keywords: school; teacher; education; youth